Leading from the liturgy: Ordained ministers as facilitators of a communal process of interpretation - den Hertog, Rein (Ecclesial Futures, 2022)
This article seeks to contribute to the reflection on ecclesial ministry from the perspective of the missio Dei. The gateway chosen is the unconventional image of ecclesial ministry as depicted in the Polish film Corpus Christi. Jan Komasa, the director, paints the protagonist as a facilitator of a communal process of interpretation and reconciliation through which the core of the gospel becomes concretely visible in social reality. This cinematographic portrayal of ecclesial ministry is then used to look at the situation regarding ministry in a small Reformed denomination in the Netherlands. The issues highlighted in Corpus Christi also play a role in these churches. To see if the imagination of Corpus Christi can also be made fruitful for thinking through Reformed theology of ministry, two steps are then taken. First, it will be shown that within the Reformed tradition there are starting points for the view of the ordained minister as a facilitator the process of interpretation. Then, using the thoughts of Michael Moynagh, the article explores how this vision of ministry can be made fruitful for the current missionary situation in the West. The article concludes with three elements needed to implement the image of the ordained minister as an interpretive guide.